2018
DOI: 10.3389/fmed.2018.00247
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis: Review and Update

Abstract: Background: Eosinophilic esophagitis (EoE) was first described in the 1990s, showing an increasing incidence and prevalence since then, being the leading cause of food impaction and the major cause of dysphagia. Probably, in a few years, EoE may no longer be considered a rare disease.Methods: This article discusses new aspects of the pathogenesis, symptoms, diagnosis, and treatment of EoE according to the last published guidelines.Results: The epidemiological studies indicate a multifactorial origin for EoE, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 161 publications
3
96
0
Order By: Relevance
“…There is a real need for noninvasive methods of diagnosing these eosinophilic gastrointestinal disorders and for biomarkers for multiple eosinophilic diseases. As an example, eosinophilic esophagitis is a disease that has emerged in the past 30 years, is associated with food allergy, afflicts children and adults, and can be diagnosed only by symptoms and histology of esophageal biopsy . More nuanced phenotyping of peripheral blood eosinophil activation status might limit the need for invasive endoscopy for tissue sampling, especially in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a real need for noninvasive methods of diagnosing these eosinophilic gastrointestinal disorders and for biomarkers for multiple eosinophilic diseases. As an example, eosinophilic esophagitis is a disease that has emerged in the past 30 years, is associated with food allergy, afflicts children and adults, and can be diagnosed only by symptoms and histology of esophageal biopsy . More nuanced phenotyping of peripheral blood eosinophil activation status might limit the need for invasive endoscopy for tissue sampling, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…(C) Histograms of side-scatter intensity for untreated control (black) and sample exposed to eotaxin for 5 h (red), r d = 0.47. [Color figure can be viewed at wileyonlinelibrary.com] with food allergy, afflicts children and adults, and can be diagnosed only by symptoms and histology of esophageal biopsy (41). More nuanced phenotyping of peripheral blood eosinophil activation status might limit the need for invasive endoscopy for tissue sampling, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…Familial occurrence is fairly frequent (10% of cases) [14]. Many studies put an emphasis on the role of genetic disorders such as Single Nucleotide Polymorphisms (SNPs) in the eotaxin-3 gene on the chromosome 7q11, polymorphism of the transforming growth factor β1 (TGF-β1) gene on the chromosome 19q33, and the polymorphism of the TSLP gene on the chromosome 5q22 [11]. Avila-Castellano et al reported that a genetic variation in the Tolllike receptor 3 (TLR3) may be a major factor predisposing to EoE [15].…”
Section: Aetiology and Pathogenesismentioning
confidence: 99%
“…and "Do you cut the food into very small pieces?" [11]. These simple questions can be very helpful in the diagnostic process.…”
Section: Clinical Picturementioning
confidence: 99%
See 1 more Smart Citation